The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jum.14911
|View full text |Cite
|
Sign up to set email alerts
|

Ankle and Foot Ultrasound: Reliability of Side‐to‐Side Comparison of Small Anatomic Structures

Abstract: Objectives In sonography of clinically relevant small structures of the ankle and foot, the healthy contralateral side can be used as a reference to identify subtle abnormalities. Intrasubject side‐to‐side variability must be minimal. The aim of this study was to assess the reliability of side‐to‐side sonographic evaluation of small structures of the ankle and foot. Methods Thirty healthy volunteers were prospectively studied. Small structures of the ankle and foot were evaluated bilaterally by 2 musculoskelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Musculoskeletal ultrasound is a valuable diagnostic tool as it allows for high resolution visualization of soft tissue structures with decreased cost, portability, dynamic examination, and comparison to the contralateral side. [36][37][38][39] In a series of 98 foot and ankle patients, sonography changed the diagnosis or treatment in 64% and influenced both diagnosis and treatment in 43%. 39 Of the 7% who underwent surgery, intraoperative and sonographic diagnoses were identical.…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal ultrasound is a valuable diagnostic tool as it allows for high resolution visualization of soft tissue structures with decreased cost, portability, dynamic examination, and comparison to the contralateral side. [36][37][38][39] In a series of 98 foot and ankle patients, sonography changed the diagnosis or treatment in 64% and influenced both diagnosis and treatment in 43%. 39 Of the 7% who underwent surgery, intraoperative and sonographic diagnoses were identical.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the studies recommended intraoperative ultrasound to follow the trajectory of the nerve and distance between the needle and the SN. 6,21,22 With the help of ultrasound, Kammar et al 6 reported that the SN trajectory showed significant variations in adults. They found that the nerve passes 5.8 mm away from the tendon at 8 cm proximal to its insertion, while it passes only 0.8 mm away as it passes at the level of 11th cm.…”
Section: Discussionmentioning
confidence: 99%
“…The US diagnosis of deltoid ligament tears may be challenging, given its anatomical complexity and variability. A recent study emphasized the importance of evaluating the healthy contralateral side as a reference [93].…”
Section: Ankle and Footmentioning
confidence: 99%